Penentuan Prioritas Perbaikan Jalan Menggunakan Fuzzy C-Means : Studi Kasus Perbaikan Jalan Di Kota Samarinda - Novianti Puspitasari; Rosmasari Rosmasari; Stefanie Stefanie (Jurnal Teknologi dan Sistem Komputer, 2017)
One of the factors traffic accidents is caused by a damaged road. Therefore, road improvements based on the priorities scale is indispensable. This study implements the Fuzzy C-means method. The method is capable of classifying data based on the characteristics. The results showed that the FCM algorithm was able to classify the road improvements into four groups; 1, 2, 3, and 4 priorities. Based on the test results the accuracy of calculations on the data of road damage, there are 8 correct data from 9 trial data or 88.89%, which indicates that the method FCM clustering results and a precise calculation.